2015
DOI: 10.1007/s00702-015-1441-1
|View full text |Cite
|
Sign up to set email alerts
|

Modern treatment in Parkinson’s disease, a personal approach

Abstract: There are many guidelines available concerning the treatment of Parkinson's disease. Most of these advocate treating young-onset patients with a dopamine agonist and older patients with levodopa. The rationale behind this recommendation has its origins in the side effects associated with each of these drug classes: whilst levodopa leads to dyskinesia, which may not be relevant for patients with a limited life-expectancy, dopamine agonists have a much longer plasma half life which probably leads to more continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 62 publications
0
16
0
3
Order By: Relevance
“…). These findings indicate that fingolimod might be beneficial for non‐motor symptoms of PD symptoms, which are a primary therapeutic challenge in PD (Reichmann ).…”
Section: Discussionmentioning
confidence: 89%
“…). These findings indicate that fingolimod might be beneficial for non‐motor symptoms of PD symptoms, which are a primary therapeutic challenge in PD (Reichmann ).…”
Section: Discussionmentioning
confidence: 89%
“…7,8 All 3 have the ability to apply a more continuous stimulation, thereby reducing motor fluctuations. 10,11 The EARLYSTIM study found improved QOL, compared to medical therapy, when introducing DBS in younger patients with PD. Randomized controlled studies have shown reduced time in "off" periods and increased time in "on" periods, without troublesome dyskinesia, in patients with PD with motor fluctuations.…”
Section: Csai and Lcigmentioning
confidence: 99%
“…68, 69 Al considerar los efectos secundarios asociado a los AD (como somnolencia, ortostatismo, alucinaciones y desordenes en el control de los impulsos), hoy en día se ha tomado una postura moderada, en donde se reconoce que existe un lugar tanto para la levodopa (aún el antiparkinsónico más potente) como para los AD en el tratamiento de la EP.…”
Section: La Revista Movement Disorders Publicó En 2011unclassified